Optical Coherence Tomography Angiography in idiopathic retinal vasculitis, aneurysms and neuroretinitis (IRVAN) syndrome: A case report. Issue 1 (January 2022) - Ouederni, Meriem; Sassi, Hela; Chelly, Zied; Nefaa, Fehmy; Cheour, Monia
Purpose: Since its first description by Chang et al. in 1995, the diagnosis of Idiopathic retinal vasculitis, aneurysms and neuroretinitis (IRVAN) syndrome has been based on the findings of Fundus Fluorescein Angiography (FFA). Our purpose was to describe the utility of optical coherence tomography angiography (OCT-A) in its diagnosis and management. Case description: A 40-year-old female presented with bilateral blurred vision. Her best corrected visual acuity was at 8/10. Fundus examination revealed blurred disc margins, perivascular exudates, arterial sheaths and retinal hemorrhages bilaterally. FFA showed staining of the optic disc with dye leakage in the right eye, a punctuate hyperfluorescence of the temporosuperior artery in the left eye, bilateral vascular sheathing and capillary dropout. OCT-A showed simultaneous presence of papillary aneurysm and neovascularization of the optic nerve head in the right eye, a papillary aneurysm in the left eye and bilateral capillary non-perfusion. Our patient was diagnosed with IRVAN syndrome. Oral steroids associated with panretinal laser photocoagulation and intravitreal injection of bevacizumab in the right eye resulted in vanishing of the papillary neovascularization with no recurrence on OCT-A at 10-month follow-up. Conclusions: OCT-A is an additional tool to FFA for visualization of arterial macroaneurysms and retinal neovascularization without the interference of dye leakage. It well demarcates nonperfused areas and ensures follow-up of retinal neovascularization. Its limitations are the limited field of view and the low sensitivity in detecting arteriolar dilations. Thus, OCT-A is unable to outplace FFA but should be considered alternately with it for non-invasive follow-up of IRVAN syndrome.